Sensitivity of Pregnant Mice to Intravenous Tissue Thromboplastin - Coccheri, S; Ollendorff, P; Astrup, T (Thrombosis and Haemostasis, 1969)
Pregnant mice are more susceptible to the intravenous injection of tissue thromboplastin than nonpregnant mice. This was true whether death of the animal, or the appearance of neurological symptoms, was used as indicator of toxicity. Increase of fibrinogen concentration or prior injection of plasmin or of a protease inhibitor (trypsin inhibitor from bovine lung) did not influence the immediate toxic effects. The reason for the increased sensitivity of pregnant mice to tissue thromboplastin remains undisclosed. Inhibition of tissue thromboplastin by serum is a slow process. The reported increase in inhibition of tissue thromboplastin by serum from pregnant individuals could not be confirmed.